EGALITARIAN NARRATIVES: WOMEN’S REPRESENTATION IN MUNIN BARUA’S FILMOGRAPHY - Sarma, Debashis Pratim (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Commercial films in India wield significant influence as a medium of communication. Other than providing entertainment, these films reflect the views of the society. While representation of women in Indian film is dubbed as scarce and superficial, this paper attempts to understand the cinematic representation of violence against women in the select films of Assamese filmmaker Munin Barua. The study employs Altaf Mazid’s egalitarianism as the theoretical framework to examine the women characters in Munin Barua’s films. The select films were analysed using Braun and Clarke's provided steps, leading to the identification of themes that revolved around women. The findings of the study reveal that women in Barua's films are frequently presented as mere plot devices, conforming to traditional gender roles. The select films of Barua also exhibit an underlying inclination towards portraying women in an egalitarian manner.